2019
DOI: 10.1038/s41419-019-2085-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of STAT3 in tubular epithelial cells prevents kidney fibrosis and nephropathy in STZ-induced diabetic mice

Abstract: Recent evidences indicate that signal transducer and activator of transcription 3 (STAT3) is one of the crucial signaling pathways in the progression of diabetic nephropathy (DN). Here, we investigated the hypothesis that pharmacological blockade of STAT3 limits the progression of DN. Treatment with selective STAT3 inhibitor, S3I-201 for 16 weeks significantly attenuated kidney injuries in streptozotocin (STZ) induced diabetic mice, associated with downregulated expression of TGF-β1, ACE/AT1, and VEGF in diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 34 publications
1
53
0
1
Order By: Relevance
“…In models of fibrosis, the increased TGF-β1 expression [ 20 ] and the subsequent collagen I production were attributed to STAT3 [ 21 ]. In the present work, decreasing the expression of phospho-STAT3 may account for the protection against the development of kidney fibrosis and in turn the progression of kidney diseases, as previously shown by [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 73%
“…In models of fibrosis, the increased TGF-β1 expression [ 20 ] and the subsequent collagen I production were attributed to STAT3 [ 21 ]. In the present work, decreasing the expression of phospho-STAT3 may account for the protection against the development of kidney fibrosis and in turn the progression of kidney diseases, as previously shown by [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 73%
“…It is important to note that the inflammatory response runs through the entire process of renal fibrosis. A large amount of pathological evidence showed that the fibrotic lesions were often distributed along the blood vessels [ 19 , 20 ]. Inflammatory microenvironment is closely related to endothelial function injury: the higher the concentration of local inflammatory factors, the more active fibrous hyperplasia, suggesting the important role of inflammatory response in renal fibrosis [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selective compounds targeting JAK2 (AG-490/tyrphostin) [269], JAK1/2 (/baricitinib) [270,271], STAT1 (fludarabine) [272] and STAT3 (nifuroxazide, S3I-201) [273] reduced albuminuria, inflammatory infiltrate, renal damage (mesangial expansion, oxidative stress, tubular atrophy, and fibrosis) and serum amyloid A in experimental DN. New design compounds such as the bromodomain inhibitor MS417 have shown the capacity to directly target acetyl-lysine residues of STAT3 and to reduce proteinuria and kidney damage in db/db mice [274].…”
Section: Jak/statmentioning
confidence: 99%